A study on warehouse management system at northport container terminal in port Klang / Nor Fadzilah Mohd Taib - Mohd Taib, Nor Fadzilah (1993)
Northport Container Terminal (NCT) started its business in September 1989 with 12 acres in area to be used. Today, this area was expanded to 25 acres in area. At present the company offers the following services to the container industry :- - storage - cleaning - tank cleaning - maintenance and repair - empty container transp{5^atl.on" - stuffing and unstuffing" - warehousing This study will look at the warehouse management in NCT. NCT started warehouse and container freight station (CFS) operations in January 1992. NCT warehouse is located in Northport, Port Klang and 0.5 km from Klang Container Terminal (KCT). NCT has two buildings which are used as warehouses. One is an old building and the other one is the new building. The old one is used to store big, unfragile or inexpensive goods such as timber, drums and chemical goods. The new warehouse is used to store small items, fragile or